2010
DOI: 10.1111/j.1444-0938.2009.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Interocular differences of the Pentacam measurements in normal subjects

Abstract: Purpose:The aim of this study was to determine the interocular differences of the Pentacam corneal measurements in a normal population. Methods: A retrospective analysis was performed on 550 eyes of 275 consecutive subjects evaluated for refractive surgery at the Rassoul Akram Hospital, Iran University of Medical Sciences. A Pentacam Scheimpflug camera was used for corneal measurements. Statistical analysis was performed to determine the normal levels of the difference between the two eyes. Results: One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
30
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 23 publications
7
30
1
Order By: Relevance
“…Distance was the only variable that did not show statistically significant difference between the better and worse eyes of the keratoconic patients (P = 0.22). The mean intereye asymmetry in volume at 3 mm central in the normal group was 0.07 mm 3 , similar to 0.06 mm 3 reported in a previous study, 25 and in the keratoconus group 0.15 mm 3 , demonstrating that there is a greater intereye asymmetry in the keratoconus group consistent with the characteristics of keratoconus as a bilateral, asymmetric, slowly progressive disorder in which the cornea has central or paracentral thinning, 1 resulting in asymmetry of the corneal volume.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Distance was the only variable that did not show statistically significant difference between the better and worse eyes of the keratoconic patients (P = 0.22). The mean intereye asymmetry in volume at 3 mm central in the normal group was 0.07 mm 3 , similar to 0.06 mm 3 reported in a previous study, 25 and in the keratoconus group 0.15 mm 3 , demonstrating that there is a greater intereye asymmetry in the keratoconus group consistent with the characteristics of keratoconus as a bilateral, asymmetric, slowly progressive disorder in which the cornea has central or paracentral thinning, 1 resulting in asymmetry of the corneal volume.…”
Section: Discussionsupporting
confidence: 88%
“…When evaluating posterior elevation, the mean intereye asymmetry in the normal group at the posterior corneal elevation was 3.75 mm in accordance with 3.62 mm reported by Falavarjani et al, 25 at the maximum posterior elevation; and the mean intereye asymmetry in the keratoconus group was 20.08 mm. A cutoff value of 6.5 mm in the mean intereye asymmetry at the posterior elevation had an AUROC value of 0.91, with 85% sensitivity and 88% specificity, discriminating these 2 groups.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous reports addressed the elevation of the posterior corneal surface to provide diagnostic cues as an earlier sign of keratoconus. [16][17][18] In the present study, ROC curve analyses with reference to keratoconic staging according to the Amsler-Krumeich classification indicated that the AUC did not differ significantly between anterior and posterior corneal surfaces in advanced keratoconus, whereas the assessment of posterior elevation was most important for the early detection of keratoconus. A combination of the curvature map and height data has promise for an improvement in diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 73%
“…First, the assessment of corneal refractive parameters allows examiners to have more control over refractive error progress. CCT considered as a major factor in keratoconus diagnosis (Falavarjani et al, 2010;Fahd et al, 2014), precise IOP measurement, and early detection of open-angle glaucoma (Channa et al, 2009). Anterior chamber parameters could be helpful to IOL power calculation of cataract patients (Shankar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%